Spontaneous outbreak of Yersinia enterocolitica infection and co-infection with Escherichia coli in black-tufted marmosets (Callithrix penicillata) - Lemos, Gisele Augusta Amorim de; Pires, Bárbara Giglio; Mainardi, Raffaella Menegheti; Chideroli, Roberta Torres; Pereira, Ulisses de Padua; Bracarense, Ana Paula Frederico Rodrigues Loureiro (Brazilian Journal of Veterinary Pathology, 2021)
Yersiniosis is a zoonotic bacterial disease that affects humans and animals, including primates. The aim of the study was to report one case of fatal Yersinia enterocolitica infection and two cases of co-infection with Escherichia coli in captive black tufted marmosets (Callithrix penicillata) in Apucarana, Paraná, south Brazil. The affected animals presented severe diarrhea and progressed to death. Gross examination showed multifocal to coalescing necrosis in the liver, mild diffuse hepatomegaly, mild diffuse necrotizing enteritis, moderate splenomegaly and focally extensive hyperemia of the leptomeninges. Microscopically, the liver lesions comprised multifocal areas of lytic necrosis with intralesional colonies of gram-negative coccobacilli, characterizing a severe, random, multifocal to coalescing necrotizing hepatitis. A moderate multifocal lymphocytic cholangiohepatitis, severe focally extensive mucosal necrosis in the small intestine, and mild multifocal lymphoplasmacytic leptomeningitis in the brain were observed. Two cases of co-infection by Y. enterocolitica and E. coli, and one case by Y. enterocolitica were confirmed through bacterial culture, biochemical characteristics and 16S rRNA. To the best of the author’s knowledge, it is the first report of an infection of Y. enterocolitica and co-infection with E. coli in black-tufted marmosets resulting in diarrhea, septicemia and death .